Distributional Effects of Public Educational Expenditures: Empirical Results from Cohort Analysis - Sheikh, Md. Rashidul Islam (Advances in Social Sciences Research Journal, 2021)
This article scanned the empirical analysis of the distributional effects of public education expenditure using Gini coefficient of education based on cross-sectional data across cohorts in Bangladesh. The main purpose of this study was to investigate whether education expenditure plays a role as a catalyst to diminish education inequality across the country by increasing years of schooling across levels of education. The Data set proved that overall years of schooling increased while education expenditure increases for a long time having slight fluctuations. Consequently, the Gini coefficient of education gradually increased and the inequality of education getting narrowed down across levels of education. Distributional effects of public expenditure on education across cohorts produced an exceptionally good result indicating positive relationships between years of schooling and the Gini coefficient of education. Despite the achievements of the education sector, the government of Bangladesh has comprehended that in the public sector education, there are substantial numbers of challenges make it tough to get the best outcomes along with quality education and insufficient budget flow across levels of education. This paper tended to uncover education redistributive policy and the existence of inequality in the cohorts across levels of education by estimating the Gini coefficient of education in Bangladesh.